Mewujudkan Sifat Zuhud Pada Mahasiswa Melalui Bimbingan Kelompok Berbasis Hadist - Jannati, Zhila; Hamandia, Muhammad Randicha (Kuras Institute, 2020)
Zuhud is a very important trait for individuals in dealing with a world that is so tiring and exhausting for humans. Zuhud will bring peace of mind and peace of mind. The purpose of this study was to find out how to realize the zuhud nature of students through hadith-based group guidance. This research uses a qualitative approach. The sample in this study was determined through a sampling technique, namely purposive sampling technique. The sample in this study were 10 students of the Islamic Guidance and Counseling Study Program, Faculty of Da'wah and Communication, UIN Raden Fatah Palembang. Data collection techniques in this study using interview techniques and observation techniques. In this study, the data were analyzed using qualitative descriptive analysis. The results obtained from this study are that the zuhud nature of students can be realized well where students are able not to feel happy about something they have and not feel sad if something is not owned; not feeling restless when insulted and not proud of being praised; and his heart is merely planted with fear, longing, and love for Allah SWT. So, it can be concluded that the zuhud nature of students can be realized by implementing hadith-based group guidance.